Evaluating Liberalization and Protectionism Approaches in African Aviation Industry: A Tourism Perspective - Banda, Sydney; Lambulira, Mathews; Bello, Felix Gasten (E-Journal of Tourism, 2024)
Abstract This study investigated the perceptions of tourism and aviation key stakeholders towards the performance of Malawi flag carrier airline, attitudes towards protectionism, and views on liberalization in the country's aviation industry. Utilising qualitative methods, the data was collected from key stakeholders within the aviation and tourism sectors in Malawi. The findings of the study highlight partial protectionism and liberation in Malawi aviation industry. The findings also reveal a diverse range of opinions towards protectionism and liberation among industry players, reflecting both positive and negative perspectives, with a prevailing inclination towards supporting the liberalization of the aviation sector. The study identified mixed perceptions regarding the performance of Malawi national airline, primarily characterized by negative viewpoints. In light of these findings, it is recommended that the national airline should continue fostering strategic partnerships with reputable international airlines, implement training programmes aimed at enhancing the skills and expertise of airline personnel, striking a balance between protectionism and fair market competition, and promote collaboration between the aviation and tourism sectors. The study also recommends the full implementation of the Yamoussoukro Declaration, which aims to liberalize air transport services across Africa, to foster regional integration and enhance the competitiveness of Malawi aviation industry.